2016
DOI: 10.1016/j.jid.2016.06.624
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Sclerodermatous Graft-Versus-Host Disease in Mice by Niclosamide

Abstract: Sclerodermatous graft-versus-host disease, a frequent complication of allogeneic hematopoietic stem cell graft, shares many features with systemic sclerosis, such as production of autoantibodies and fibrosis of skin and inner organs. Recent reports on the implication of signal transducer and activator of transcription 3 and of Wnt/β-catenin in fibrosis have prompted us to investigate the effects of the inhibition of both signaling pathways in a mouse model of sclerodermatous graft-versus-host disease, using ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…In addition, our results are in agreement with previous studies that showed that ATO decreases the T cell response during MLR, as assessed by the production of IFN-g and increased apoptosis of T cells in a dosedependent manner (40,41). Our in vitro results allowed us to further assess the effect of the co-treatment of ATO and Cu 2+ in a mouse model of chronic GvHD (42,43). The co-treatment significantly reduced the GvHD phenotype of diseased mice.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, our results are in agreement with previous studies that showed that ATO decreases the T cell response during MLR, as assessed by the production of IFN-g and increased apoptosis of T cells in a dosedependent manner (40,41). Our in vitro results allowed us to further assess the effect of the co-treatment of ATO and Cu 2+ in a mouse model of chronic GvHD (42,43). The co-treatment significantly reduced the GvHD phenotype of diseased mice.…”
Section: Discussionsupporting
confidence: 91%
“…Our in vitro results allowed us to further assess the effect of the co-treatment of ATO and Cu 2+ in a mouse model of chronic GvHD ( 42 , 43 ). The co-treatment significantly reduced the GvHD phenotype of diseased mice.…”
Section: Discussionmentioning
confidence: 99%
“…Solid black arrows indicate GvHD pathology, including high infiltration of mononuclear cells in hepatic and lung tissues, shortening and/or structural abnormality of intestinal villi, and bronchial luminal narrowing. [55][56][57][58][59] The corresponding number at each scale bar indicates an image size (mm). was demonstrated in a previous study, 68 suggesting the feasibility of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…(D) Histopathology of intestine, liver, and lung tissues obtained from all groups. Solid black arrows indicate GvHD pathology, including high infiltration of mononuclear cells in hepatic and lung tissues, shortening and/or structural abnormality of intestinal villi, and bronchial luminal narrowing [55][56][57][58][59]. The corresponding number at each scale bar indicates an image size (mm).…”
mentioning
confidence: 99%
“…This disease is a leading cause of morbidity and mortality after such transplant [91] . Morin et al reported that niclosamide treatment provided beneficial immunological effects and reversed clinical symptoms of graft-versus-host disease, including alopecia, vasculitis, and diarrhea, and also prevented fibrosis of the skin and visceral organs in the sclerodermatous graft-versus-host disease model using BALB/c mice provoked by B10.D2 bone marrow and spleen cell transplantation [92] . The beneficial effects of niclosamide were associated with inhibition of STAT3, Wnt/β-catenin, ERK 1/2, AKT, and Notch signaling pathways in earlobe skin of mice.…”
Section: Niclosamide and Sclerodermatous Graft-versus-host Diseasementioning
confidence: 99%